When Teamwork Works: Examining the Relationship Between Leader-Member Exchange Differentiation and Team Creativity - Du, Juan; Lin, Xinyue; Cai, Yahua; Sun, Fufu; Amankwah-Amoah, Joseph (Frontiers in Psychology, 2022)
Drawing on team creativity literature and social comparison theory, we investigate how leader-member exchange (LMX) differentiation influences team creativity. Using a survey based on 91 R&D teams from Chinese companies, we observe that LMX differentiation is negatively related to team creativity (β = −0.35, p < 0.01). More importantly, we demonstrate that team behavioral integration mediates the relationship between LMX differentiation and team creativity (indirect effect size = −0.72, with 95% CI of −1.91, −0.13), and team emotional intelligence (TEI) moderates the relationship between LMX differentiation and team behavioral integration (β = 0.23, p < 0.05), such that LMX differentiation has a weaker negative influence on team behavioral integration when TEI is higher. These results provide relevant suggestions for organizational team building, management, and development.